Intrauterine exposure to tobacco and executive functioning in high school. (1st July 2017) - Rose-Jacobs, Ruth; Richardson, Mark A.; Buchanan-Howland, Kathryn; Chen, Clara A.; Cabral, Howard; Heeren, Timothy C.; Liebschutz, Jane; Forman, Leah; Frank, Deborah A.
Highlights: High School teachers masked to study objectives rated executive functioning (EF). Intrauterine tobacco exposure associated with less optimal behavioral regulation. <0.5 pack tobacco exposure resulted in 2–3 times greater odds executive dysfunction. Neither other intrauterine nor environmental exposures predicted less optimal EF. Prenatal counseling should emphasize all legal and illegal substance abstinence. Abstract: Background: Executive functioning (EF), an umbrella construct encompassing gradual maturation of cognitive organization/management processes, is important to success in multiple settings including high school. Intrauterine tobacco exposure (IUTE) correlates with negative cognitive/behavioral outcomes, but little is known about its association with adolescent EF and information from real-life contexts is sparse. We evaluated the impact of IUTE on teacher-reported observations of EF in urban high school students controlling for covariates including other intrauterine and adolescent substance exposures. Methods: A prospective low-income birth cohort (51% male; 89% African American/Caribbean) was followed through late adolescence (16–18 years old). At birth, intrauterine exposures to cocaine and other substances (52% cocaine, 52% tobacco, 26% marijuana, 26% alcohol) were identified by meconium and/or urine assays, and/or maternal self-report. High school teachers knowledgeable about the student and unaware of study aims were asked to complete the Behavior Rating Inventory of Executive Functioning-Teacher Form (BRIEF-TF) annually. Results: Teachers completed at least one BRIEF-TF for 131 adolescents. Multivariable analyses included controls for: demographics; intrauterine cocaine, marijuana, and alcohol exposures; early childhood exposures to lead; and violence exposure from school-age to adolescence. IUTE was associated with less optimal BRIEF-TF Behavioral Regulation scores (p <0.05). Other intrauterine substance exposures did not predict less optimal BRIEF-TF scores, nor did exposures to violence, lead, nor adolescents' own substance use. Conclusions: IUTE is associated with offspring's less optimal EF. Prenatal counseling should emphasize abstinence from tobacco, as well as alcohol and illegal substances.